Plan de Negocio para el Montaje y la Creación del Restaurante “Museo Tradición”, especializado en comida típica local en la Ciudad de Santa Marta Magdalena - Hernández Pardo, Marily Ester; Pérez Márquez, Laila Samira (Universidad Antonio Nariño, 2022)
The proposal of this present project is the assembly and creation of a typical restaurant of the Caribbean coast that seeks to differentiate itself from others in the city, both in service, quality, and in the different gastronomic offers that it will offer. This business idea arose because the city of Santa Marta does not have a restaurant that specifically offered or honored local gastronomy as a business model, the restaurant industry has high competition in the market, for that reason it is important innovate to satisfy consumers. As a restaurant, the commercial process will be forced to update both products and processes, and in turn implement technology, seeking to offer truly innovative and differentiating elements to aim for a very good future positioning; The research will be of a non-experimental nature and the data processing model will address a mixed recognition scheme.